(3GdUdGHI GdfaSjI h YdGbJgG HOaGYjI GdGfLGR dOi dGYHj cQI GdbOe Ufa GcGHQ GdfGTWjf aj GdQGHWI GdLRGFQjI GdeMJQaI GdGhdi s - (3LGeY, M GdCejfs; (3Hf Ycj, CejQIs; (3eYgO GdJQHjI GdHOfjI h GdQjGVjI, LGeYI GdLRGFQ (B3 s ((3GdLRGFQ s, 2024)
(3gOaJ gPg GdOQGSI Edi GdJYQa Ydi GdUdGHI GdfaSjI hYdGbJgG HOGaYjI GdEfLGR dOi dGYHj cQI GdbOe Ufa CcGHQ GdfGTWjf aj GdQGHWI GdLRGFQjI GdeMJQaI GdChdi ddehSe GdQjGVj (B2022/2023(3, hdJMbjb Pdc Je GdGYJeGO Ydi GdefgL GdhUaj HEJHGY GdCSdhH GdGQJHGWj, hbO Jchf eLJeY GdOQGSI ef (B400 (3dGYH cQI GdbOe, hGdYjfI TedJ (B208 (3dGYH Je GNJjGQge HWQjbI YThGFjI WHbjI, bGe GdHGMK HJUeje ebjGS Yf GdUdGHI GdfaSjI hebjGS Yf OGaYjI GdEfLGR hbGe HJhRjYge Ydi YjfI GdOQGSI, hdJMdjd hJaSjQ GdfJGFL Je GdGYJeGO Ydi HQfGeL GdMReI GdEMUGFjI ddYdhe GdGLJeGYjI (B28 SPSS IBM. (3CXgQJ fJGFL GdOQGSI Cfg JhLO YdGbI GQJHGWjI WQOjI bhjI LOG OGdI EMUGFjG Hjf GdGdJRGe hOGaYjI GdEfLGR dOi dGYHj cQI GdbOe Ufa CcGHQ, hJhLO YdGbI GQJHGWjI WQOjI bhjI OGdI EMUGFjG Hjf GdJMce hOGaYjI GdEfLGR dOi dGYHj cQI GdbOe Ufa CcGHQ, hJhLO YdGbI GQJHGWjI WQOjI bhjI OGdI EMUGFjG Hjf GdJMOj hOGaYjI GdEfLGR dOi dGYHj cQI GdbOe Ufa CcGHQ(B. (3haj GdCNjQ Je GdJhUd Edi Cfg JhLO YdGbI GQJHGWjI WQOjI bhjI LOG OGdI EMUGFjG Hjf GdUdGHI GdfaSjI hOGaYjI GdEfLGR dOi dGYHj cQI GdbOe Ufa CcGHQ, hefg fSJfJL Cfg cdeG RGOJ GdUdGHI GdfaSjI dOi dGYHj cQI GdbOe Ufa CcGHQ RGOJ OGaYjI GdEfLGR dOjge(B. s
(3OcJhQGIs
Keywords: (3GdJMVjQ GdfaSj GdQjGVj s; (3GdJQHjI GdHOfjI h GdQjGVjIs; (3GdUdGHI GdfaSjIs; (3OGaYjI GdGfLGRs; (3cQI GdbOes